The sex difference in 6-month MACEs and its explaining variables in acute myocardial infarction survivors: Data from CPACS-3 study. (15th July 2020) - Sun, Yihong; Feng, Lin; Li, Xian; Gao, Runlin; Wu, Yangfeng
Abstract: Background: We aimed to assess sex difference in developing major adverse cardiovascular events (MACEs) after discharge and factors associated with the gender disparity among AMI survivors. Methods: We selected the patients hospitalized with either NSTEMI or STEMI from 101 Chinese centers in the CPACS 3 study. We compared sex differences in MACEs and mortality in 6 months after discharge using a Cox proportional hazards model, following sequential adjustment for covariates. Results: 8958 patients with AMI were included and 30.3% were women. Overall, the crude rate of MACEs at 6 month for women were significantly higher than men (6.5% vs 4.5%; hazard ratio (HR) =1.47; 95% CI, 1.21–1.77). Women also had significantly higher total mortality compared to men (4.4% vs 2.7%; HR = 1.65; 95% CI, 1.30–2.09). Among possible explanatory factors, patients' cardiovascular risk profile might explain 53%, age 38%, low level of education and socioeconomic status 32%. Interestingly, medications at discharge did not contribute to the sex disparity in 6-month risk of MACEs. These factors could explain a similar proportion of the gender disparity in total death. All together, these factors could explain all the disparity in the risk of both MACEs (HR = 1.05, 95% CI, 0.85–1.31) and total death (HR = 1.00, 95% CI, 0.76–1.30). Conclusions: The gender disparity in MACEs and total death among AMI patients continues at 6 months after discharged surviving. Multiple factors could explain the higher risk for women, including poorer cardiovascular risk factor profile, older age and lower socioeconomic status. Trial Registration: CPACS-3 was registered on www.clinicaltrails.gov, and the registration number is NCT01398228 . Highlights: Woman with AMI has both higher mortality and MACEs at 6 month after discharge. The gender disparity related to CV risk, education and socioeconomic status The secondary prevention medication not related to 6 month outcomes